Integrated localization theory of translation studies - Odacıoğlu, Mehmet Cem; Odacıoğlu, Mehmet Cem (My University, 2017)
As with every other discipline, Informatics and Communication Technologies have also begun to affect translation studies. In this context, this study covers a part of my doctoral thesis written on the topic and is based on the debate about whether existing translation theories need to be revised in accordance with current conditions. The study contends that, as with other translation theories developed for specialized translation areas, the ‘localization industry’ that initially became popular in the late 1980s and for which attempts have been made, by those conducting this study and some translation scholars, to include it under the umbrella of translation studies in the belief that it would be a gain for translation studies, requires a new translation theory. Accordingly, this study intends to build a bridge between translation studies and the theory of localization, which has emerged as an industrial discourse. A theoretical proposal called the ‘integrated localization theory’ of translation studies has also been proposed in the study. Furthermore, it is considered that this theoretical proposal will not discredit the existing translation theories that have emerged in different periods and show the characteristics of paradigms, but will instead combine and harmonize them. With this approach, localization may even be transformed into one of the new paradigms of translation studies.
Keywords: Integrated localization theory; Localization industry; Informatics and communication technologies; Localization theory; Entegre yerelleştirme teorisi; Yerelleştirme endüstrisi; Bilişim ve iletişim teknolojileri; Yerelleştirme teorisi